2019
DOI: 10.1186/s12871-019-0796-5
|View full text |Cite
|
Sign up to set email alerts
|

Association of Mallampati scoring on airway outcomes in women undergoing general anesthesia with Supreme™ laryngeal mask airway in cesarean section

Abstract: Background Obstetric dfficult airway is a leading cause of maternal morbidity and mortality. The laryngeal mask airway (LMA) is often used as a rescue airway device after failed intubation, however, little is known about predictors of difficult LMA insertion, particularly in obstetrics. Since Mallampati scores of III/IV has been associated with difficult tracheal intubation, our present study aims to investigate if Mallampati score (MP) could predict airway outcomes for LMA use in obstetrics. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(23 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…However, Boutonnet et al reported that Mallampati scores remain unchanged for 37% of parturients in labor [7], and our study may not be adequately powered to detect a significant change in Mallampati scores. Nonetheless, we have previously shown that Mallampati scores of 3 or 4 did not significantly affect time to effective ventilation, first attempt failure rate, or sLMA seal pressure compared to parturients with Mallampati scores of 1 or 2 undergoing cesarean delivery [21].…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…However, Boutonnet et al reported that Mallampati scores remain unchanged for 37% of parturients in labor [7], and our study may not be adequately powered to detect a significant change in Mallampati scores. Nonetheless, we have previously shown that Mallampati scores of 3 or 4 did not significantly affect time to effective ventilation, first attempt failure rate, or sLMA seal pressure compared to parturients with Mallampati scores of 1 or 2 undergoing cesarean delivery [21].…”
Section: Discussionmentioning
confidence: 78%
“…This is a secondary analysis of a prospective cohort study investigating the use of sLMA during cesarean delivery [18]. With this dataset, we had previously published the association of Mallampati scores on airway outcomes with sLMA use for cesarean delivery [21]. Approval was obtained from the Institutional Review Board at the Quanzhou Women's and Children's Hospital, Fujian Province, China, (dated 11 Nov 2013) and registered with clinicaltrials.gov (NCT02026882) on 3 January 2014.…”
Section: Methodsmentioning
confidence: 99%
“…However, since 2001, the use of SGA as primary airway device during GA for CD has been demonstrated in several studies and been reviewed on several occasions [8][9][10][11][12][13][14][15][16][17]19,43 && ,44,45 && ,46]. To date, there are at least twelve peer reviewed studies describing the use of SGA as primary airway device (Table 1) [8][9][10][11][12][13][14][15][16][17][18][19]. Eight articles describe the use of SGA as a primary airway device during elective CDs under GA [8,9,[11][12][13][14]18,19], three studies report the use of SGA in elective and emergency caesarean deliveries [10,16,17] and one study in emergency cases only [15].…”
Section: Supraglottic Airway Devices As Primary Devices In Obstetric ...mentioning
confidence: 99%
“…To date, there are at least twelve peer reviewed studies describing the use of SGA as primary airway device (Table 1) [8][9][10][11][12][13][14][15][16][17][18][19]. Eight articles describe the use of SGA as a primary airway device during elective CDs under GA [8,9,[11][12][13][14]18,19], three studies report the use of SGA in elective and emergency caesarean deliveries [10,16,17] and one study in emergency cases only [15]. Cricoid force was applied in all but one study during induction of GA, but its use during the maintenance phase of anaesthesia was variable, with some releasing it after insertion of the SGA or if ventilation was compromised and others releasing after the delivery of the baby.…”
Section: Supraglottic Airway Devices As Primary Devices In Obstetric ...mentioning
confidence: 99%
See 1 more Smart Citation